2013
DOI: 10.1016/j.jand.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Eating Breakfast and Dinner Together as a Family: Associations with Sociodemographic Characteristics and Implications for Diet Quality and Weight Status

Abstract: Background Research has shown that adolescents who frequently share evening meals with their families experience more positive health outcomes, including diets of higher nutritional quality. However, little is known about families eating together at breakfast. Objectives This study examined sociodemographic differences in family meal frequencies in a population-based adolescent sample. Additionally, this study examined associations of family breakfast meal frequency with dietary quality and weight status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
100
2
22

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(142 citation statements)
references
References 40 publications
18
100
2
22
Order By: Relevance
“…This result corroborates prior research showing that the frequency of breakfast family meals and total weekly family meals are positively associated with better diet quality for elementary age children and adolescents 3,4,10,13,22,28,42 and extends previous studies by showing preschool children receive dietary benefits from breakfast family meals too. This result is also consistent with previous literature showing that associations between family meals and diet quality are more likely to be observed among non-Hispanic children compared to Hispanic children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result corroborates prior research showing that the frequency of breakfast family meals and total weekly family meals are positively associated with better diet quality for elementary age children and adolescents 3,4,10,13,22,28,42 and extends previous studies by showing preschool children receive dietary benefits from breakfast family meals too. This result is also consistent with previous literature showing that associations between family meals and diet quality are more likely to be observed among non-Hispanic children compared to Hispanic children.…”
Section: Discussionsupporting
confidence: 91%
“…“how often did most of your family members eat…” vs. “how often did your family eat…”) could explain some differences between groups. 39 In addition, although 24-hour dietary recalls are a stronger measure than self-report dietary intake, they still have inherent limitations such as, day to day variability as well as larger errors for foods with higher caloric density. Another limitation is that other important variables that could impact the association between family meals and diet quality such as acculturation and parenting practices (e.g., parent feeding practices, parent modeling of healthy eating) were not assessed, due to not having similar measures across the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study only asked about family dinner frequency, rather than frequency of all family meals, family dinners capture most meals eaten together. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, research about family mealtime factors that may vary according to time of day and have the potential to influence the overall experience (e.g., perceived importance of eating together, interpersonal interactions at the meal, structure of the meal) or more directly the types and amounts of food consumed (e.g., where food is purchased, how it is served, adolescent involvement in meal preparation) at family breakfast meals is lacking in the peer-reviewed literature (10, 11) . A search of the literature identified only three previous studies that have examined how eating breakfast together with one's family may be related to nutrition outcomes (10, 12, 13) ; just one of these three studies reported on the eating habits of U.S. adolescents (10) and no studies reported on youth residing in rural areas. There is a particular need to better understand the experience of eating together at breakfast among rural U.S. families as school breakfast participation is lower in rural as compared to urban areas (14) , and the potential for informing interventions addressing dietary patterns and the high prevalence of weight-related problems and food insecurity among rural youth (15-19) .…”
Section: Introductionmentioning
confidence: 99%